2016
DOI: 10.1007/s12539-016-0185-4
|View full text |Cite
|
Sign up to set email alerts
|

LPRP: A Gene–Gene Interaction Network Construction Algorithm and Its Application in Breast Cancer Data Analysis

Abstract: The importance of the construction of gene–gene interaction (GGI) network to better understand breast cancer has previously been highlighted. In this study, we propose a novel GGI network construction method called linear and probabilistic relations prediction (LPRP) and used it for gaining system level insight into breast cancer mechanisms. We construct separate genome-wide GGI networks for tumor and normal breast samples, respectively, by applying LPRP on their gene expression datasets profiled by The Cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The GoogleNet architecture on the other hand is a much deeper and wider architecture with 22 layers, while still having considerably lower number of parameters (5 million parameters) in the network than AlexNet (60 million parameters). An application of the “network in network” architecture (Lin et al, 2013 ) in the form of the inception modules is a key feature of the GoogleNet architecture. The inception module uses parallel 1 × 1, 3 × 3, and 5 × 5 convolutions along with a max-pooling layer in parallel, hence enabling it to capture a variety of features in parallel.…”
Section: Methodsmentioning
confidence: 99%
“…The GoogleNet architecture on the other hand is a much deeper and wider architecture with 22 layers, while still having considerably lower number of parameters (5 million parameters) in the network than AlexNet (60 million parameters). An application of the “network in network” architecture (Lin et al, 2013 ) in the form of the inception modules is a key feature of the GoogleNet architecture. The inception module uses parallel 1 × 1, 3 × 3, and 5 × 5 convolutions along with a max-pooling layer in parallel, hence enabling it to capture a variety of features in parallel.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, sparse models would be less sensitive to global changes in the topology of the network 18 . Research has shown that lower global clustering coefficients, that is, networks with more random connections, may help to explain the occurrence of brain disability, gene‐gene interactions in cancer and disease transmission 27‐29 …”
Section: Discussionmentioning
confidence: 99%
“…18 Research has shown that lower global clustering coefficients, that is, networks with more random connections, may help to explain the occurrence of brain disability, gene-gene interactions in cancer and disease transmission. [27][28][29] As contemporary paintings, networks may not be fully understood at first glance. Centrality measures provide additional information on the relative position and influence of nodes representing variables in the overall network structure, which aids observers to interpret the models.…”
Section: Discussionmentioning
confidence: 99%
“…Su et al combine interaction networks with known breast cancer genes to identify potential drug targets [37]. Their Linear and Probabilistic Relations Prediction (LPRP) first creates a gene-gene interaction network from the given RNAseq data set and enhances it with network information from Pathway Commons [38].…”
Section: Related Workmentioning
confidence: 99%